40 years of the quantum Hall effect - Von Klitzing, Klaus; Chakraborty, Tapash; Kim, Philip; Madhavan, Vidya; Dai, Xi; Mciver, James; Tokura, Yoshinori; Savary, Lucile; Smirnova, Daria; Rey, Ana Maria; Felser, Claudia; Gooth, Johannes; et al. (Nature Reviews Physics, 2020)
The discovery of the quantum Hall effect (QHE) marked a turning point in condensed-matter physics. The measurement of the Hall resistance showed that electronic resistance could be defined precisely in terms of fundamental constants, even in a disordered and irregular sample. Over the past 40 years, the QHE has inspired new theories and led to experimental discoveries in a range of fields going beyond solid-state electronics to photonics and quantum entanglement. In this Viewpoint, physicists reflect on how the QHE has influenced their research.
CRIS-Team Scopus Importer:2022-04-14